2021
DOI: 10.1101/2021.05.07.442906
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Striatin 3 and MAP4K4 cooperate towards oncogenic growth and tissue invasion in medulloblastoma

Abstract: Proliferation and motility are mutually exclusive biological processes associated with cancer that depend on precise control of upstream signaling pathways with overlapping functionalities. We find that STRN3 and STRN4 scaffold subunits of the STRIPAK complex interact with MAP4K4 for pathway regulation in medulloblastoma. Disruption of the MAP4K4-STRIPAK complex impairs growth factor-induced migration and tissue invasion and stalls YAP/TAZ target gene expression and oncogenic growth. The migration promoting fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
(195 reference statements)
0
2
0
Order By: Relevance
“…Our study identified a possible link between MAP4K4 function and FEME through the regulated PM-association of the FEME priming factors SH3KBP1, CIP4 and FBP17. We recently identified a potential interaction of MAP4K4 with SH3KBP1using a Bio-ID based approach 60 , and in this study, we found that MAP4K4 regulates CIP4 PM-association and its accumulation in cortical patches. The early endosome marker EEA1 also localizes to these patches, and it is thus possible that one aspect of FEME processing towards early endosomes occurs preferentially there.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Our study identified a possible link between MAP4K4 function and FEME through the regulated PM-association of the FEME priming factors SH3KBP1, CIP4 and FBP17. We recently identified a potential interaction of MAP4K4 with SH3KBP1using a Bio-ID based approach 60 , and in this study, we found that MAP4K4 regulates CIP4 PM-association and its accumulation in cortical patches. The early endosome marker EEA1 also localizes to these patches, and it is thus possible that one aspect of FEME processing towards early endosomes occurs preferentially there.…”
Section: Discussionmentioning
confidence: 53%
“…PM enrichment of these proteins in a MAP4K4-dependent manner in HGF-stimulated cells could indicate a link between MAP4K4 and FEME priming. Interestingly, we also detected the potential interaction of SH3KBP1/CIN85 with MAP4K4 in an unrelated proteomic interaction analysis 60 . Due to their cytoplasmic localization, we further tested whether MAP4K4 depletion alters subcellular localization of CIP4.…”
Section: Map4k4 Controls Subcellular Localization Of Cip4mentioning
confidence: 82%